Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Biochemical characterization of an aspartic protease from vigna radiata: kinetic interactions with the classical inhibitor pepstatin implicating a tight binding mechanism - Kulkarni, Aarohi; Rao, Mala (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2007)
{Aspartic proteases are the focus of recent research interest in understanding the physiological importance of this class of enzymes in plants. This is the first report of an aspartic protease from the seeds of Vigna radiata. The aspartic protease was purified to homogeneity by fractional ammonium sulfate precipitation and pepstatin-A agarose affinity column. It was found to have a molecular weight of 67,406 Da by gel filtration chromatography. SDS-PAGE analysis revealed the presence of a heterodimer with subunits of molecular weights of 44,024 and 23,349 Da respectively. The enzyme was pH stable with the amino acid analysis confirming the molecular weight of the protein. The substrate cleavage site as analyzed by using the synthetic substrate was found to be the Phe-Tyr bond. The kinetic interactions of the enzyme were studied with the universal inhibitor, pepstatin A. This is the first report on the interactions of a plant aspartic protease with pepstatin-A, an inhibitor from a microbial source. A competitive one-step mechanism of binding is observed. The progress curves are time-dependent and consistent with tight binding inhibition. The K(i) value of the reversible complex of pepstatin with the enzyme was 0.87 mu M whereas the overall inhibition constant K(i)*
Keywords: ant colony; global optimization; metaheuristics; multimodal continuous functions; particle swarm optimization

pH Induced structural alterations in an aspartic protease from Vigna radiata indicating an alkali induced molten globule state - Kulkarni, Aarohi; Gaikwad, Sushama M.; Rao, Mala (International Journal of Biological Macromolecules, 2008)
pH-dependent transitions in secondary and tertiary structure are described for a plant aspartic protease from Vigna radiata. The enzyme was pH stable with pH optima of 3.0. The Lineweaver Burk analysis at various pH yielded pK(a) values of 3.3 and 4.29 indicating acidic amino acids at the active site of the enzyme. The structural changes exemplified compact secondary structure collapsed tertiary structure and exposure of hydrophobic patches at pH 10. The changes at pH 10 are typical of a molten globule state. This alkali induced molten globule is novel since acid induced molten globule state is more reported. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkali induced molten globule; Plant aspartic protease; Structural transitions

Differential elicitation of an aspartic protease inhibitor: regulation of endogenous protease and initial events in germination in seeds of vigna radiata - Kulkarni, Aarohi; Rao, Mala (Peptides, 2009)
Plant aspartic proteases are of recent origin with their physiological significance in crucial processes emerging. Reports on the significance of aspartic protease inhibitors and their endogenous proteases in seeds of plants are scanty. This paper reports the purification of an aspartic protease inhibitor from the seeds of Vigna radiata, its control of the endogenous aspartic protease and their subsequent role in the early germination events. The role of the aspartic protease inhibitor and the enzyme in initial stages of germination of V. radiata has been tracked by differential timed expression and germination assays. The expression pattern revealed maximum expression of the inhibitor in the dormant seeds while the enzyme was predominant in the germinating seeds. Their expression patterns and interactions indicate their significance in initiation of germination. The expression of other classes of proteases was monitored during germination and a model predicting the events occurring during proteolysis of the storage protein in germination is hypothesized. The inhibitor was a linear, hydrophobic, pH stable and thermostable peptide with molecular weight of 1660 Da. The purified inhibitor showed a pI of 4.36 with the sequence as AEIYN KDGNK LDLYG. The inhibitor was found to be stable in a broad range of pH from 2 to 10 with an optimum of 3.0. The half-life of VrAPI at 100 degrees C was 30 min whereas the maximum activity was observed at 37 degrees C. The initial kinetic analysis of the inhibitor against the enclogenous protease showed an IC50 value of 11 nM while the value of the inhibition rate constant K-i was 34 x 10(-9) M. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Aspartic protease; Plant proteases; Protease inhibitors; Vigna radiata